2009
DOI: 10.1080/09540250802392257
|View full text |Cite
|
Sign up to set email alerts
|

Australian English‐language textbooks: the gender issues

Abstract: This paper examines the nature and extent of gender stereotyping, both linguistic and pictorial, in a set of 10 Australian English-language textbooks for intermediate learners. In order to determine how accurately the books reflect the status of women in contemporary Australian society a content and linguistic analysis was conducted, focusing on, amongst other things, the ratio of male to female characters, the portrayal of women and men in social and domestic settings, the use of gender-inclusive expressions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 30 publications
3
47
0
6
Order By: Relevance
“…It also sounds odd when it is used in interrogative tags: Everybody is quiet, isn't he or she? Another popular alternative nowadays is generic they despite a long history of debate with regard to its acceptability (Baron, 1986;Bodine, 1975;Burchfield, 1981;Fowler, 1965;Lee, 1999;Lee & Collins, 2009;Partridge, 1965;Pauwels, 1998Pauwels, , 2001. Nilsen (2001) comments that generic they may have come into the English language earlier if not because of the vigilance of English teachers.…”
Section: Gender and The English Languagementioning
confidence: 99%
“…It also sounds odd when it is used in interrogative tags: Everybody is quiet, isn't he or she? Another popular alternative nowadays is generic they despite a long history of debate with regard to its acceptability (Baron, 1986;Bodine, 1975;Burchfield, 1981;Fowler, 1965;Lee, 1999;Lee & Collins, 2009;Partridge, 1965;Pauwels, 1998Pauwels, , 2001. Nilsen (2001) comments that generic they may have come into the English language earlier if not because of the vigilance of English teachers.…”
Section: Gender and The English Languagementioning
confidence: 99%
“…Visual content comprises images (drawings and pictures) and videos (film and animations). In a study by Lee and Collins [35], English language textbooks were investigated for both visual content and language. They found that men were depicted as working nearly twice as often as women and that women were portrayed as victims or caring more often than men.…”
Section: Introductionmentioning
confidence: 99%
“…Stories written for children have been recognized for their power to reproduce societal norms, teaching children (and reminding adults) of what is considered normal and acceptable (Lee and Collins, 2009;Wannamaker, 2006;Zipes, 1999Zipes, , 2002. ''Literature written for children… surface[s] as cultural products tied to a discursive legacy that attempts to regulate and define children's bodies in terms of gender and sexuality'' (Marshall, 2004, p. 259).…”
Section: Gender In Children's Literaturementioning
confidence: 99%